Securinine, a novel alkaloid, regulates cell cycle and EMT in gastric cancer by inducing iron-dependent cell death - Yuan, Weiwei; Song, Hao; Shi, Yin; Han, Jianye; Jiao, Shaohe; Liang, Song; Xu, Yuanmin; Jiang, Yi; Ji, Yuehui; Chen, Zhangming; Liu, Limin; Xu, Aman; et al. (Frontiers in Oncology, 2025)
BackgroundGastric cancer remains one of the most prevalent and lethal cancers worldwide, with its insidious onset hindering early diagnosis and effective treatment. Despite advances, the overall survival rate for gastric cancer remains low, primarily due to late diagnosis, tumor heterogeneity, and resistance to current therapies. This highlights the urgent need for novel therapeutic strategies.MethodsGastric cancer cell lines were treated with securinine, followed by analysis of cell proliferation, cycle, and Epithelial-Mesenchymal Transition (EMT) using Western blot and immunofluorescence techniques. Transcriptomic analysis was performed to identify changes in ferroptosis-related iron metabolism pathways. In vivo studies were conducted using xenograft mouse models to assess tumor growth.ResultsSecurinine significantly inhibited proliferation and modulated the cell cycle, arresting cells at the G2/M transition, while also enhancing EMT, which altered cell migration and invasiveness. Transcriptomic analysis revealed that securinine activated ferroptosis-related iron metabolic pathways, upregulating key genes such as HMOX1, FTH1, and FTR. Inhibition of these genes reversed the effects on cell proliferation and EMT, highlighting the role of ferroptosis in the anticancer effects of securinine. In vivo studies demonstrated a significant reduction in tumor growth in xenograft models.ConclusionsSecurinine shows potential as a novel therapeutic agent for gastric cancer by inducing ferroptosis and modulating key cell death and survival pathways. Its ability to regulate iron metabolism and EMT suggests that it could be a promising candidate for developing new therapeutic strategies against gastric cancer, especially for drug-resistant cases.